Significant Association Between Huntingtin Gene Mutation and Prevalence of Hopelessness, Depression and Anxiety Symptoms - Butėnaitė, Adelė; Strumila, Robertas; Lengvenytė, Aistė; Pakutkaitė, Indrė Kotryna; Morkūnienė, Aušra; Matulevičienė, Aušra; Dlugauskas, Edgaras; Utkus, Algirdas (Acta medica Lituanica, 2021)
Background: In Huntington’s disease psychiatric symptoms may manifest prior to motor dysfunction. Such symptoms negatively impact people’s quality of life and can worsen the course of the primary disease. The aim of the present study was to assess and compare depression, anxiety and hopelessness rates in individuals with and without an abnormal expansion of CAG repeats in the huntingtin (HTT) gene and healthy controls. Materials and methods: Study involved 31 individuals referred for genetic testing for Huntington’s disease and a control group of 41. Depressive and anxiety symptoms were assessed using Beck Hopelessness Scale (BHS) and Hospital Anxiety and Depression Scale (HADS). Results between groups were compared using the Mann–Whitney U test. Two-sided Bonferroni corrected p-value was set at ≤0.017. Results: Individuals with HTT gene mutation (“gene mutation positive”, GMP) (N=20) scored higher on the HADS depression subscale (5.90 ± 4.52 vs 1.36 ± 1.91; p ≤ 0.017) than those without HTT gene mutation (“gene mutation negative”, GMN) (N=11). GMP and control groups scored higher than the GMN group on the BHS (5.65 ± 3.91 vs 2.09 ± 1.64 and 5.27 ± 4.11 vs 2.09 ± 1.64, respectively; p ≤ 0.017). No differences in anxiety levels were found. Conclusions: Depressive symptoms and hopelessness were more prevalent in individuals with HTT gene mutation than in individuals who were tested but had no said mutation. Such results emphasise the importance of timely diagnosis and treatment of psychiatric comorbidities in individuals affected by Huntington’s disease.